Improving adaptation to drought stress in white pea bean (Phaseolus vulgaris L.): Genotypic effects on grain yield, yield components and pod harvest index - Assefa, Teshale; Rao, Idupulapati M.; Cannon, Steven B.; Wu, Jixiang; Gutema, Zenbaba; Blair, Matthew W.; Otyama, Paul; Alemayehu, Fitsume; Dagne, Belete (Wiley, 2017)
Common bean (Phaseolus vulgaris L.) is the most important food legume crop in Africa and Latin America where rainfall pattern is unpredictable. The objectives were to identify better yielding common bean lines with good canning quality under drought, and to identify traits that could be used as selection criteria for evaluating drought-tolerant genotypes. In all, 35 advanced lines were developed through single seed descent and evaluated with a standard check under drought and irrigated conditions at two locations over 2 years in Ethiopia. Grain yield (GY), pod number per m2, seed number per m2 and seed weight decreased by 56%, 47%, 49% and 14%, respectively, under drought stress. Eight genotypes had better yield with good canning quality under drought compared to the check. Moderate to high proportion of genetic effects were observed under drought conditions for GY and yield components compared to genotype × environment effects. Significant positive correlations between GY and pod harvest index (PHI) in drought suggest that PHI could be used as an indirect selection criterion for common bean improvement.